South African Television Moves into the Global Age - Teer-Tomaselli, Ruth (The Routledge Companion to Global Television, 2019)
Television delivery throughout the world has changed rapidly over the past two decades. Within South Africa, much of this global narrative is repeated. The last 25 years saw a move from a single monopoly broadcaster within the ‘public service’ tradition (but later subsumed into the apartheid political agenda), to the present situation of a multi-company, multi-platform, increasingly digital delivery, calling into question even the very definition of ‘broadcasting’. ‘Global difference’ in South Africa plays out through a relatively late start but surprisingly short catch-up period, emphasizing a demographic/socio-economic specificity that has resulted in a highly skewed television market in which the uptake of high-end technology is less widespread than in other more ‘developed’ markets, and where the taste of local programming dominates even the technologically advanced sectors. The move toward a digital system, together with the introduction of competition, has provided challenges to the regulatory regime. The majority of the audience share, however, remains with local programming, regardless of its delivery.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Curating Life, Staging Art: Modernisms and the Art Practices of Television - Makhubu, Nomusa (The Routledge Companion to Global Television, 2019)
Television is predisposed to the perception that it is the opposite of art and politics and that it is a time-consuming means for “dumbing down,” placating, disempowering and benumbing the citizenry. Through a discussion of the place of art and that of television, I use, as a conceptual framework, the convergence of the white cube and the black box to interrogate dynamics of postcoloniality, vision and power and how this forged divergent modernisms. Television in Africa did not, as with postwar America, create a sense of collective communities of spectatorship that would be brought closer to art appreciation through television. Rather, television, as the political, social and cultural phenomenon of modernization in various African countries, seemed to corrupt what was regarded as “pristine” cultural practices. However, since it coincided with colonial independence and the emergence of postcolonial nations, it became intertwined with various modes and mediums through which new forms of social consciousness aimed at self-definition and self-representation could be disseminated. The convergence of the white cube spaces of art and the black box of television enables an engagement with the colonial spatio-temporal distanciation of Africa from the global stage.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (lieu de production du savoir); _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Research Methodologies - Chilisa, Bagele (SAGE, 2020)
Author Bagele Chilisa updates her groundbreaking textbook to give a new generation of scholars a crucial foundation in indigenous methods, methodologies, and epistemologies. Addressing the increasing emphasis in the classroom and in the field to sensitize researchers and students to diverse perspectives - especially those of women, minority groups, former colonized societies, indigenous people, historically oppressed communities, and people with disabilities, the second edition of Indigenous Research Methodologies situates research in a larger, historical, cultural, and global context to make visible the specific methodologies that are commensurate with thetransformative paradigm of social science research"
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; _Nettoyé

Unpacking Culture: Art and Commodity in Colonial and Postcolonial Worlds - Phillips, Ruth B.; Steiner, Christopher Burghard (University of California Press, 1999)
Tourist art production is a global phenomenon and is increasingly recognized as an important and authentic expression of indigenous visual traditions. These thoughtful, engaging essays provide a comparative perspective on the history, character, and impact of tourist art in colonized societies in three areas of the world: Africa, Oceania, and North America. Ranging broadly historically and geographically, Unpacking Culture is the first collection to bring together substantial case studies on this topic from around the world.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé